2014
DOI: 10.2527/jas.2013-7279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Criollo breed Romosinuano as purebred and crossbred cows with Brahman and Angus in Florida: I. Reproduction and parturition1,2,3

Abstract: The objectives of this work were to compare reproduction and parturition traits of the Criollo breed Romosinuano as straightbred and crossbred cows with Angus and Brahman, to estimate heterosis and direct and maternal genetic breed effects, and to describe calf loss, cow removals from the project, the occurrence of calving difficulty, inadequate calf vigor at birth, and udder problems by cow breed groups. Cows (n = 404) were born from 2002 to 2005. After their first exposure to bulls as young cows, in all subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…This relative positioning of means in both experiments may highlight the more favorable performance of Romosinuano cows in a more temperate region; could it conversely suggest that Angus cows were more adapted to the conditions in Florida than in Arkansas? Such a notion, though not well supported, is intriguing given the background of the research Angus herd in Florida (Riley et al, 2007(Riley et al, , 2011(Riley et al, , 2014. In a subset of the purebred Angus and Romosinuano cows in this study, the Angus cows appeared to be more susceptible to the toxins in the tall fescue and heat stress during summer months than the Romosinuano cows (Burke et al, 2010).…”
Section: Calving and Weaning Ratementioning
confidence: 63%
See 4 more Smart Citations
“…This relative positioning of means in both experiments may highlight the more favorable performance of Romosinuano cows in a more temperate region; could it conversely suggest that Angus cows were more adapted to the conditions in Florida than in Arkansas? Such a notion, though not well supported, is intriguing given the background of the research Angus herd in Florida (Riley et al, 2007(Riley et al, , 2011(Riley et al, , 2014. In a subset of the purebred Angus and Romosinuano cows in this study, the Angus cows appeared to be more susceptible to the toxins in the tall fescue and heat stress during summer months than the Romosinuano cows (Burke et al, 2010).…”
Section: Calving and Weaning Ratementioning
confidence: 63%
“…The direct Romosinuano effects were favorable (Table 3; P o0.003). No breed type differences in calving and weaning rate were detected in evaluation of these groups and neither heterosis effects nor direct Romosinuano effects differed from 0 in Florida (Riley et al, 2014). This estimate of heterosis is at the upper range of values reported for Bos taurus cows (e.g., Cundiff et al, 1992;Newman et al, 1993) and was as high as many reported Bos indicus-British cross estimates (e.g., Cartwright et al, 1964;Prayaga, 2004).…”
Section: Calving and Weaning Ratementioning
confidence: 65%
See 3 more Smart Citations